DIGITAL TECHNOLOGIES IN THE EDUCATIONAL PROCESS: OPPORTUNITIES AND QUALITY INDICATORS (Universal International Scientific Journal, 2026)
This article highlights the importance of family, school, and community cooperation in the education of the younger generation based on the views of Abdulla Avloni. It also analyzes the effective use of modern digital technologies and information and communication tools in the educational process, the formation of media literacy, time management, and information immunity among students. It is emphasized that the use of the principle of demonstration in the educational process and the capabilities of modern educational platforms serve the intellectual development of young people.
Keywords: : Education, Abdulla Avloni, digital technologies, information and communication technologies, media literacy, the principle of demonstration, information immunity, modern educational platforms, youth education, family and school cooperation.